Pediatric Ileocolica Invagination: A Case Report - Sulaiman Yusuf; Tita Menawati Liansyah (Britain International for Academic Research (BIAR) Publisher, 2020)
Invagination or intussusception is an inversion of intestinal segments into other intestinal segments which is the most common cause of intestinal obstruction in infants and children. Early diagnosis and therapy can cause intestinal ischemia, perforation, and peritonitis which can be fatal. Trias classic symptoms consist of abdominal pain, vomiting, and blood in the stool. Invagination often occurs in children under 2 years old, with the highest incidence in children aged 4 - 9 months. The most common cause of invagination is idiopathic. Reportedly a boy, 10 months with a history of mucus with blood, vomiting, flatulence, history of colds cough. Physical examination reveals that the child is aware and active. The abdomen appears distended, palpable mass such as sausages, and intestinal hyperperistaltic. In the rectal toucher, there is mucus and blood on the handscoon. Investigations found anemia and leukocytosis. Stool examination showed blood, erythrocytes 4-6 LPB and leukocytes 8-10 LPB. Radiological examination of the abdomen appears to dilate the intestine (colon) with a coffee bean sign, the impression is in accordance with the picture of invagination. Abdominal ultrasound impression according to the picture of invagination (colo-colica). The patient was diagnosed as ileocolica intussusception and acute diarrhea without dehydration.